1992
DOI: 10.3168/jds.s0022-0302(92)77773-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fat and Emulsifiers on the Efficacy of Nisin in Inhibiting Listeria monocytogenes in Fluid Milk

Abstract: The recent FDA affirmation of nisin, an antimicrobial peptide, as a GRAS (generally recognized as safe) additive in pasteurized cheese spreads has renewed interest in its potential application in US dairy products. Fluid milks were prepared with varying concentrations of milk fat (0 to 12.9%) and of nisin (0 to 50 U/ml). Biological activity assays using a sensitive indicator microorganism in a well diffusion system indicated that initial nisin activity (50 U/ml) decreased by about 33% when it was added to skim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
113
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(119 citation statements)
references
References 21 publications
5
113
0
1
Order By: Relevance
“…The addition of 160 AU ml -1 cerein 8A produced by B. cereus to UHT milk resulted in a decrease of 3 log cycles in the cell counts of L. monocytogenes within the 14-day period at 4 °C (BIZANI et al, 2008). Nisin (50 IU ml -1 ) caused 7, 3, and 1 log reduction in the counts of L. monocytogenes Scott A in skim milk (0% fat), milk with 4% fat, and milk containing 12.9% fat, respectively (JUNG et al, 1992). Most of the studies declared that cell counts of L. monocytogenes in milk challenged with different concentrations of nisin (BHATTI et al, 2004;KIM et al, 2008;YOON et al, 2011) or pediocin 5 (HUANG et al, 1994) decreased to an undetectable level at the beginning of the incubation, but then increased during the incubation period.…”
Section: Effect Of Bacteriocins On the Survival Of L Monocytogenes Imentioning
confidence: 97%
See 1 more Smart Citation
“…The addition of 160 AU ml -1 cerein 8A produced by B. cereus to UHT milk resulted in a decrease of 3 log cycles in the cell counts of L. monocytogenes within the 14-day period at 4 °C (BIZANI et al, 2008). Nisin (50 IU ml -1 ) caused 7, 3, and 1 log reduction in the counts of L. monocytogenes Scott A in skim milk (0% fat), milk with 4% fat, and milk containing 12.9% fat, respectively (JUNG et al, 1992). Most of the studies declared that cell counts of L. monocytogenes in milk challenged with different concentrations of nisin (BHATTI et al, 2004;KIM et al, 2008;YOON et al, 2011) or pediocin 5 (HUANG et al, 1994) decreased to an undetectable level at the beginning of the incubation, but then increased during the incubation period.…”
Section: Effect Of Bacteriocins On the Survival Of L Monocytogenes Imentioning
confidence: 97%
“…This result indicates that lactococcin BZ could be a good alternative antimicrobial agent to control pathogens in foods containing fat. Similar to enterocin KP, the inhibitory activity of nisin (JUNG et al, 1992;BHATTI et al, 2004;MEENA et al, 2004;YOON et al, 2011) and pediocin 5 from Pediococcus acidilactici UL5 (HUANG et al, 1994) declined by increasing fat content of dairy products. According to those authors, the decrease in bacteriocin activity was probably due to the fact that bacteriocin might be adsorbed to the milk fat globules and become unavailable to destroy bacterial cells.…”
Section: Effect Of Bacteriocins On the Survival Of L Monocytogenes Imentioning
confidence: 97%
“…17,18 Nevertheless, loss of antimicrobial activity was reported when nisin was directly added to foods. Jung et al 19 found significant loss of nisin activity in milk because of interactions with milk fat globules. Apparently, nisin preferentially adsorbed at the milk fat droplet surface to maximize interaction of the hydrophobic side chains with lipid phase molecules.…”
Section: Introductionmentioning
confidence: 98%
“…The polypeptide nisin is a GRAS (generally recognized as safe) additive (Jung et al, 1992) which shows antimicrobial activity chiefly against a range of Gram positive bacteria, particularly spore-formers {Delves-Broughton, 1990). The potential applications of nisin in food preservation i.e.…”
Section: Introductfonmentioning
confidence: 99%